Dielectric Relaxation Study of Polar Liquids Using Time Domain Reflectometry Technique - Sonwane, Prashant; Kamble, Siddharth; Khirade, P.W. (Asian Journal of Chemistry, 2012)
Complex permittivity of binary mixture of 2-methoxyethanol-propanol mixture for various temperatures was obtained in the frequency range of 10 MHz to 10 GHz using the time domain reflectometry technique. The static dielectric constant (es) and relaxation time (t) have been obtained from complex permittivity spectra using non-linear list square fit method. This values are used for the calculation of access permittivity es, excess inverse relaxation time (1/t)E, Kirkwood correlation factor (geff) Bruggeman factor (fB) and thermodynamic parameters. On the basis of above parameters, information on the molecular structure and dynamics of the mixture have been discussed.